Effectiveness Test of Melon Fruit Peel Ethanol Extract Cream (Cucumis melo) on Incision Wound Healing of White Rats (Rattus norvegicus) - Rizki, Husna; Harlita, Harlita (Biology, Medicine, & Natural Product Chemistry, 2025)
Incision wounds are a type of open wound that requires treatment to prevent infection and accelerate healing. Using natural ingredient-based creams has become a more practical alternative to conventional ointments. Melon rind (Cucumis melo) contains active compounds such as tannins, flavonoids, and phenols that have anti-inflammatory and antimicrobial properties, potentially accelerating wound healing and reducing the risk of infection. This study aims to test the effectiveness of melon rind ethanol extract cream on incision wound healing in white rats (Rattus norvegicus). The study used an experimental method with three treatment groups: control (bacitracin), 15% melon peel extract cream (P1), and 25% melon peel extract cream (P2). Mice were adapted for 7 days before the treatment test. The cream was applied three times a day for 14 days, and wound diameter and body weight were observed every two days. Observation data were analysed using one way ANOVA test version 26.0. The results showed that melon rind extract cream had physical characteristics that met the standards. ANOVA and LSD tests on wound diameter showed significant differences between control and treatment, although there was no significant difference between P1 and P2. Meanwhile, the ANOVA and LSD test results on body weight showed significant differences between groups. Group P2 showed a steady increase in body weight, indicating the safety of the cream.